2020
DOI: 10.1111/ajr.12590
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal violence and violent re‐injury in the Northern Territory

Abstract: Objectives To analyse incidence of prior emergency department presentations for interpersonal violence and demographics for a series of hospital admissions for interpersonal violence injuries. Design Retrospective analysis of trauma registry. Setting A tertiary hospital and primary referral centre for trauma in the Top End of the Northern Territory. Participants Patients hospitalised from 2010 to 2015 for injuries due to interpersonal violence with an injury severity score > 9. Main outcome measures Patient de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In remote areas, there were an average of 202 incidents per 1000 population, compared to average of 782 per 1000 population in urban areas [ 117 ]. Furthermore, a retrospective analysis of data specific to Royal Darwin Hospital (the sole trauma referral centre in the NT), from the Australia New Zealand Trauma Registry found that in the NT, being injured from intimate partner violence in an urban or remote, as opposed to very remote, location carried higher odds of previous presentations with intimate partner violence [ 118 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In remote areas, there were an average of 202 incidents per 1000 population, compared to average of 782 per 1000 population in urban areas [ 117 ]. Furthermore, a retrospective analysis of data specific to Royal Darwin Hospital (the sole trauma referral centre in the NT), from the Australia New Zealand Trauma Registry found that in the NT, being injured from intimate partner violence in an urban or remote, as opposed to very remote, location carried higher odds of previous presentations with intimate partner violence [ 118 ].…”
Section: Discussionmentioning
confidence: 99%
“…The completeness of reporting of events is also an important factor when considering the non - attenders cluster, as data collection may be limited by service availability if the regions with poorer school attendance also have a more general limit on services including fewer potential CPS reporters. It has been suggested that intimate partner violence, for instance, may be under-reported in very remote settings [ 118 ]. This is less likely in the case of child maltreatment, firstly given NT mandatory reporting laws require every person in the NT to report child abuse or neglect, and secondly given the transparency provided by communal living in remote communities, it is likely that most maltreated children will be recorded, even if not every event [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ramifications, in addition to recidivism, include lower rates of employment, greater risks for complications, more chronic pain, and lower patient satisfaction among patients with pre-existing mental illness [ 4 , 20 , 23 29 ]. Resources to treat this patient population are lacking in most trauma systems, and this remains a major public health issue [ 5 , 14 , 17 , 30 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trauma patients have been shown to exhibit recidivism frequently, resulting in new traumatic injuries, seen in subsequent visits to emergency rooms [ 1 5 ]. These visits and resultant hospital admissions generate substantial medical and interpersonal costs.…”
Section: Introductionmentioning
confidence: 99%
“…The integrative review by Carvalho AP et al 13 included 19 studies and showed that alcohol consumption is the predictor of physical violence in the perpetrator and for the adolescent victim of the violence. Lim KHA et al 12 found that majority of the victims of IPV presented to the emergency department had a history of alcohol intake. Blunt force or impact injuries (lacerations at 43.12%, contusion at 31.87% and abrasion at 27.5%) were the commonest in the patients of IPV in the current study.…”
Section: Discussionmentioning
confidence: 99%